More than Means: Characterizing Individual Differences in Pupillary Dilations. (December 2020) - Sibley, Ciara; Foroughi, Cyrus K.; Brown, Noelle L.; Phillips, Henry; Drollinger, Sabrina; Eagle, Michael; Coyne, Joseph T.
This study sought to characterize individual differences in pupillary dilations during a simple cognitive task. Eighty-four Navy and Marine Corps student pilots performed a digit memory recall test while their pupillary data were recorded. Results showed that peak pupil sizes significantly increased with difficulty of the memory task, however variability in pupillary dilations was substantial, with only 51% of individuals' data corresponding with the aggregate results and dilations varying between participants by as much as 1 millimeter. The analyses presented in this paper illustrate the large individual variability that exists in pupil data, between individuals and even within individuals on a trial by trial basis. This work serves as a benchmark for understanding variability in pupillary dilations and encourages follow on work to explore casual mechanisms of differences in pupil dilations across individuals, especially before using pupil data for applied purposes.